An investigation into the challenges encountered by high high school students in mountains areas in writing in English : - Lê, Thị Hồng Cẩm (Can Tho University, 2016)
The key aims of this research are to investigate into the challenges encountered by high high school students in mountains areas in writing in English and to find out sources for such challenges